Pelvic floor disorders in women with gynecologic malignancy. Issue 6 (December 2018) - Hall, Evelyn; Robison, Katina; Wohlrab, Kyle
Abstract : Purpose of review: This article serves as an update on issues relating to the intersection of pelvic floor disorders and gynecology oncology. Recent findings: Gynecologic cancer survivors experience pelvic floor disorders (PFDs) at a higher rate than their age-matched peers, often because of shared risk factors and as sequelae of cancer treatment. Concomitant pelvic floor and oncologic surgery can serve as a method to promote quality of life. Studies have demonstrated concomitant surgery to be well tolerated in appropriately selected patients, but only about 2% of oncologic surgeries are coordinated to include the treatment of PFDs. Conversely, women undergoing surgery for PFD have a low, but real risk of occult malignancy. Therefore, preoperative counseling is warranted in select populations. This article will discuss the management of concurrent PFDs and gynecologic malignancies. Summary: Healthcare providers should be familiar with screening, management and referral of women with pelvic floor disorders in the gynecologic oncology population.